Can firm profitability, firm sustainability, and firm size influence director remuneration in public listed companies? - K Ghani, Erlane; Muhammad, Kamaruzzaman; Saidatul Shahnaz Mohsin, Wan; Pratama, Arie (Edelweiss Applied Science and Technology, 2024)
A director of a company shall exercise reasonable care, skill, and diligence with the knowledge, skill, and experience that may reasonably be expected of a director and which the director in fact has. In view of this, there is a need to find a balance between remunerating directors for their challenging responsibilities and attracting and retaining them, while also justifying the pay package to shareholders, which remains difficult for many listed companies. Therefore, it is important to understand the factors that influence directors’ remuneration in public listed companies. This study aims to address this issue by choosing three firm characteristics namely, firm profitability, firm sustainability, and firm size. This study relied on content analysis on public listed companies in Malaysia. This study utilised 291 observations over a period of 3 years, from 2019 to 2021. The statistical analysis was performed using panel data analysis. This study shows that firm sustainability positively and significantly influences director remuneration in public listed companies. On the other hand, this study shows that firm profitability and firm size negatively influence director remuneration, although the relationship is not significant. The findings of this study implicate that firm sustainability is an important factor in determining director remuneration in public listed companies. The findings of this study contribute to the literature on the factors that contribute to director remuneration in public listed companies and are able to justify why these directors are remunerated differently.